2020
DOI: 10.1001/jamanetworkopen.2020.2370
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cannabis Withdrawal Symptoms Among People With Regular or Dependent Use of Cannabinoids

Abstract: IMPORTANCE Cannabis withdrawal syndrome (CWS)-a diagnostic indicator of cannabis use disorder-commonly occurs on cessation of heavy and prolonged cannabis use. To date, the prevalence of CWS syndrome has not been well described, nor have the factors potentially associated with CWS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 108 publications
(66 citation statements)
references
References 105 publications
1
64
0
Order By: Relevance
“…It was associated with mood/anxiety/personality disorders, significant disability and family history of depression. A recent systematic review and meta-analysis reported a 17% prevalence in population-based samples [ 107 ]. The criteria for cannabis withdrawal are listed in Table 6 .…”
Section: Resultsmentioning
confidence: 99%
“…It was associated with mood/anxiety/personality disorders, significant disability and family history of depression. A recent systematic review and meta-analysis reported a 17% prevalence in population-based samples [ 107 ]. The criteria for cannabis withdrawal are listed in Table 6 .…”
Section: Resultsmentioning
confidence: 99%
“…Cannabis addiction is known to feature periods of cannabinoid withdrawal marked by agitation and manifest sympathetic hyperstimulation [106]. Sympathetic stimulation has been shown to have direct adverse activities on the stem cell niche of the hair follicle [107] and likely acts similarly in other stem cell niches.…”
Section: Pathways and Mechanismsmentioning
confidence: 99%
“…Slower titration can be considered if the patient experiences significant cannabis withdrawal effects (e.g., insomnia, anxiety, increased pain); however, this is not typical if using the proposed taper and dosing regimen outlined above. Withdrawal is usually seen with more regular THC dosing (Struble et al, 2019;Bahji et al, 2020), and more commonly in recreational populations.…”
Section: Step 6-consider Stopping the Trial And Discontinuing Cannabis If No Responsementioning
confidence: 99%